VD_FINDINFO Faillite / 2018 / 16 vom 29. August 2018 - VD Tribunal cantonal (2018)
CONCORDAT ORDINAIRE, HOMOLOGATION DU CONCORDAT, ABUS DE DROIT, ASSEMBLÉE DES CRÉANCIERS, POSTPOSITION | 2 al. 2 CC, 298 al. 2 LP, 306 al. 1 ch. 1 LP, 306 al. 1 ch. 3 LP, 307 LP, 320 CPC (CH)